A caporettói áttörés (1917) - Pintér, István (Közép-Európai Közlemények, 2009)
Scientists of military history have already analyzed several important battles of the First World War, but still there are some blank parts and debatable issues. Our paper presents one of them: the breaking through of the Austrian-Hungarian and German army at Caporetto in October, 1917. We try to give a general overview of the issue by critically presenting the relevant literature and the different points of view.